轴装式串联少齿差行星传动装置的运动分析及仿真 - 李君; 陈小安; 韩贤武; 罗文军; 陈勇 (Jixie Chuandong, 2008)
The structural characteristic of a spindle-set series few teeth difference epicyclic gear transmission system is expounded,the multi-input or multi-output transmission characteristic and the velocity ratiosare.For demonstrating the systemic transmission characteristic,the motion simulation and results analysis to every input-output type are realized based on ADAMS platform under combining with three-mensional simulation model in Unigraphic.The simulation results are in accord with the theoretical analysis ones.The results also show that it is practical to the new system kinematics analysis through the virtual prototype.